Olivine-phyric basalt in the Mesoproterozoic Gawler silicic large igneous province, South Australia: Examples at the Olympic Dam Iron Oxide Cu-U-Au-Ag deposit and other localities - Huang, Q.; Kamenetsky, V.; Ehrig, K.; McPhie, J.; Kamenetsky, M.; Cross, K.; Meffre, S.; Agangi, Andrea; Chambefort, I.; Direen, N.; Maas, R.; Apukhtina, O. (Elsevier BV, 2016)
The felsic-dominant Gawler Range Volcanics and cogenetic Hiltaba Suite granitoids constitute the ca. 1590 Ma Gawler silicic large igneous province in the Gawler Craton, South Australia. The province includes minor occurrences of olivine-phyric basalt at Kokatha and Mount Gunson. In this study, we describe additional olivine-phyric basalts and dykes intersected by drill holes at the Olympic Dam Iron Oxide Cu–U–Au–Ag deposit and the Wirrda Well Cu–Au prospect. Laser Ablation Inductively Coupled Plasma Mass Spectrometry U–Pb dating results (un-anchored) of apatite in the basalts and dykes at Mount Gunson (1576 ± 33 Ma), Wirrda Well (1596 ± 17 Ma), and Olympic Dam (1621 ± 20 Ma) confirm their effective temporal correlation with the ca. 1590 Ma Gawler silicic large igneous province. Compositions of Cr-spinel inclusions enclosed in former olivine phenocrysts (forsterite number >80) in basalts at Mount Gunson, Wirrda Well and Olympic Dam imply derivation from a heterogeneous mantle source that may have been modified by subduction. Least-altered olivine-phyric basalts at Mount Gunson and Kokatha are characterized by negative Nb and Ta anomalies, which are typical of arc basalts but are also common in back-arc basin basalts, in accordance with the result suggested by the Cr-spinel source indicator. The mafic components of the Gawler Range Volcanics generally have higher Zr contents and Zr/TiO2 ratios than those of high-Mg basalts and picrites produced in variable tectonic settings worldwide, possibly reflecting continental crustal components involved in their mantle source.High abundances (typically ~20 vol.%) of former olivine phenocrysts in the basalt at Olympic Dam imply high-Mg whole-rock compositions and a high temperature of the primary magma. This result is consistent with previous models in which the heat flux from mantle magmas caused large-scale partial melting of crustal rocks that subsequently gave rise to silicic magmas erupted and intruded to form the Gawler silicic large igneous province.